Student's creativity through the guided discovery-based task to eliminate mathematics difficulties - Soewardini, Herfa Maulina Dewi; Meilantifa, Meilantifa; Rofiki, Imam (International Journal on Teaching and Learning Mathematics, 2022)
Many students had difficulties in learning mathematics. The students have a problem in determining the divided lines, the height lines, and the weight lines in triangles by using the term. The lack of creativity is also a factor in the difficulty. This study aims to find out the creativity of students through the guided discovery-based task of the line in the triangle to eliminate the stress learning the material. The method used activity observation in completing the work by drawing according to the student's creativity indicator and the guided discovery-based task about a step of the divided lines, the height lines, and the weight lines in a triangle. It also uses task-based interviews. The result of the observation is that the students perform the activities according to the guided discovery step, namely stimulation, problem statement, data collection, data processing, verification, and generalization. Some students fall into the creative category. The result of the interview shows that students' difficulties eliminated with guidance according to guided discovery step. The conclusion is that students are creative with guided discovery based on the task of the concept of the triangle and can eliminate the difficulty of mathematics.